Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1017/s001216220300063x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of suck and swallow rhythms during feeding in preterm infants with and without bronchopulmonary dysplasia

Abstract: The aim of this study was to define quantitative measures for assessing the integration and maturation of suck and swallow rhythms in preterm infants as they relate to each other. Fourteen preterm infants (eight males, six females; gestational age range 26 to 32 weeks) with bronchopulmonary dysplasia (BPD) and an age-matched cohort of 20 infants (10 males, 10 females; gestational age range 26 to 33 weeks) without BPD were studied weekly from time of initiation of oral feeding using simultaneous recordings of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
34
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 18 publications
6
34
0
1
Order By: Relevance
“…These findings are consistent with the findings of previous studies of preterm neonates, which have reported that suckling skills [6][7][8] and the coordination of suckling, swallowing and breathing [9][10][11][12][13][14][15] improve with ongoing maturity. These findings are also consistent with previous studies that have suggested that certain morbidities affecting body-systems involved in feeding, such as the respiratory and circulatory systems, may affect the efficiency of suckle-feeding in preterm neonates.…”
Section: Attainment Of Exclusive Suckle-feedssupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are consistent with the findings of previous studies of preterm neonates, which have reported that suckling skills [6][7][8] and the coordination of suckling, swallowing and breathing [9][10][11][12][13][14][15] improve with ongoing maturity. These findings are also consistent with previous studies that have suggested that certain morbidities affecting body-systems involved in feeding, such as the respiratory and circulatory systems, may affect the efficiency of suckle-feeding in preterm neonates.…”
Section: Attainment Of Exclusive Suckle-feedssupporting
confidence: 92%
“…[15][16][17][18][19][20] The results from these studies suggest that certain comorbidities affecting the respiratory and circulatory systems may affect the ability to suckle-feed in preterm neonates. [15][16][17][18][19][20] However, there is minimal information regarding the effects of morbidity affecting other body-systems involved in feeding, such as the digestive and nervous systems. In addition, there are no large studies that have specifically investigated the relationship between the overall degree of neonatal morbidity and age at commencement of suckle-feeds and/or age at attainment of exclusive suckle-feeding.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, infants are able to maintain a relatively constant milk flow and continue breathing by inserting swallows into particular regions of the extant sucking and breathing relationship. The results are consistent with and extend the findings of earlier studies (3,4,20).…”
supporting
confidence: 92%